2008
DOI: 10.1103/physreve.78.041601
|View full text |Cite
|
Sign up to set email alerts
|

Front instabilities in evaporatively dewetting nanofluids

Abstract: Various experimental settings that involve drying solutions or suspensions of nanoparticles-often called nanofluids-have recently been used to produce structured nanoparticle layers. In addition to the formation of polygonal networks and spinodal-like patterns, the occurrence of branched structures has been reported. After reviewing the experimental results we use a modified version of the Monte Carlo model first introduced by Rabani [Nature 426, 271 (2003)] to study structure formation in evaporating films of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
119
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(143 citation statements)
references
References 70 publications
21
119
3
Order By: Relevance
“…In general, most authors agree that patterns of lines that are parallel to the receding contact line result from a stick-slip motion of the contact line that is caused by pinning/depinning events [30,45,55,87]. Branched structures and patterns of lines orthogonal to the contact line (the latter are sometimes called spoke patterns [44,47,55,67,88]) are thought to result from transversal instabilities of the receding contact line (sometimes called fingering instabilities) [51,[89][90][91].…”
Section: Modelsmentioning
confidence: 99%
“…In general, most authors agree that patterns of lines that are parallel to the receding contact line result from a stick-slip motion of the contact line that is caused by pinning/depinning events [30,45,55,87]. Branched structures and patterns of lines orthogonal to the contact line (the latter are sometimes called spoke patterns [44,47,55,67,88]) are thought to result from transversal instabilities of the receding contact line (sometimes called fingering instabilities) [51,[89][90][91].…”
Section: Modelsmentioning
confidence: 99%
“…[1][2][3][4][5] The micro(nano-)graphenes originating from a top-down approach synthesis (exfoliation of graphite-based materials) usually exhibit a lower conductivity and their (transparent) conductive films formed by spin coating, hot-spray or other techniques show a few-dozen kO sheet resistance. [20][21][22] Initially, this was described by hydrodynamic instabilities and solute-transport phenomena. ); 11 this relationship can be modified by the film thickness within a given matter.…”
mentioning
confidence: 99%
“…A variant is a low surface coverage, e.g. 20,21 The recently reported ''open'' domain simulations also consider particle aggregation during the evaporation process, assisted by shrinking of the drying fronts from the edges toward the center. [12][13][14][15] At present, we propose an evaporation-induced self-assembling method as an alternative way to achieve a highly conductive graphene (few-layer graphene) network on a macroscale.…”
mentioning
confidence: 99%
“…To model these processes, simple two-dimensional (2d) lattice kinetic Monte-Carlo (KMC) models were proposed [28,26,23,29]. Vancea et.…”
Section: Introductionmentioning
confidence: 99%
“…al. [29] made a detailed investigation of the characteristics of the branched structures and their dependence on the model parameters. They observed that as in the experiments the fingering instability becomes stronger the smaller the nano-particle mobility gets.…”
Section: Introductionmentioning
confidence: 99%